Unlawful Content Online Towards a New Regulatory Framework for Online Platforms - Ullrich, Carsten (Luxemburger Juristische Studien - Luxembourg Legal Studies, 2021)
Illegal content remains a persistent and growing issue on the internet. This book reviews seven problematic areas - defamation, hate speech, terrorist content, copyright, counterfeit, unsafe products and food - to illustrate that the fight against unlawful content on online platforms in the EU is hampered by fragmented and outdated laws. Meanwhile, the global internet companies that govern our digital spaces enforce their own policies, based on commercial objectives, and with secondary regard for public values and individuals' rights. The book subsequently charts out a solution of how EU lawmakers can bring social media and the like to take on adequate responsibilities for protecting users and public interests. The author argues that a safety-by-design approach, supported by technical standards, can be an effective way for implementing these new duties. Carsten Ullrich is a legal researcher at the University of Luxembourg, where he works on the regulation of digital technologies. The doctoral thesis on which this book is based was awarded the Rolf Tarrach Prize 2021 for the best dissertation in Luxembourg.